Optimalisasi Penerimaan Negara di Tengah Kesenjangan Kepatuhan Pajak: Analisis Kritis terhadap Strategi Ekstensifikasi dan Intensifikasi Pajak - Ardita Wahyu Hidayah; Femilia Putri Hendriani; Suci Ramadhanti; Wahjoe Pangestoeti (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
State revenue from taxes plays a vital role in financing national development. However, tax realization often faces challenges in the form of low levels of taxpayer compliance, which creates a gap between potential and actual revenue. This study aims to analyze the implementation of tax intensification and extensification strategies in optimizing state revenue, including policy effectiveness, obstacles in the field, and alternative approaches to improve compliance and tax potential. This article discusses efforts to optimize state revenue through two main strategies, namely tax extensification and intensification, with reference to case studies and data from various institutions and regions. Extensification focuses on broadening the tax base through attracting new taxpayers, while intensification refers to improving the efficiency and effectiveness of collection from existing taxpayers. The analysis shows that the main obstacles in implementing these two strategies include low tax awareness, weak monitoring systems, and inconsistent data between agencies. Therefore, a more comprehensive, data-driven, and taxpayer education-oriented policy integration is needed to reduce the compliance gap and promote sustainable revenue growth.